Effect of sodium alginate and its guluronic acid/mannuronic acid ratio on the physicochemical properties of high‐amylose cornstarch. (29th March 2016) - Zhao, Yang; Chen, HaiHua; Wang, YuSheng; Li, QianQian
Abstract : To investigate the effect of sodium alginate (AGNa) and its guluronic acid/mannuronic acid (G/M) ratio on the physicochemical properties of high‐AM cornstarch (HACS), the pasting, thermal, rheological, and gelling properties of AGNa‐HACS mixtures were measured by rapid viscosity analysis (RVA), DSC, dynamic rheometry, and texture analysis. Compared with HACS alone, the peak viscosity and final viscosity of AGNa‐HACS were increased by 71–84 RVU and 97–106 RVU, respectively, the breakdown value was reduced by 20 RVU, and Δ H was increased by 2.44–3.31 J/g. The retrogradation rate of HACS after storage for 3–14 days decreased, as well the gel hardness, whereas the apparent viscosity ( ηa ) and loss tangent (tanδ) increased with the addition of AGNa. The G/M ratio of AGNa influenced the gelatinization, gelling, and retrogradation properties of HACS. The Δ H, storage modulus ( G ′), and gel hardness were increased by AGNa with a high G content. Short‐term retrogradation was retarded by AGNa with a low G acid content.